Early Post-Traumatic Seizures After Severe Traumatic Brain Injury - Matthew Pease; Jonathan Elmer; Arka N. Mallela; Jorge Gonzalez-Martinez; David O. Okonkwo; Flora Hammond; Sergiu Abramovici; James F. Castellano; Wesley T. Kerr (Neurotrauma Reports)
Seizures are common after severe traumatic brain injury (TBI), with rates in the acute period approaching 5% with seizure prophylaxis in historical clinical trials. Post-traumatic seizures (PTS) are divided into categories: immediate PTS occur prior to resuscitation, typically in the field; early PTS occur from resuscitation to 7 days post-trauma; and late PTS occur thereafter. The relationship between immediate and early PTS, as well as their risk factors, are not well studied in modern cohorts. We performed a secondary analysis of a prospective database of severe TBI patients, defined as a post-resuscitation Glasgow Coma Scale ≤8, from a single institution. For the 579 patients included, rates of immediate and early PTS were 1.6% and 3.8%, respectively. We were unable to identify any clinical correlates for immediate seizures. In contrast, early PTS were associated with age (odds ratio [OR] 1.5; 95% confidence interval [CI]: 1.1–2.0; p < 0.01), hypoxia (3.3, 95% CI: 1.2–8.5; p = 0.02), and subdural hematoma (SDH) (2.8, 95% CI: 1.0–2.8; p = 0.04) in multivariable modeling. Patients with early PTS had higher rates of status epilepticus than those with immediate PTS (45% [n = 10/22] vs. 0% [n = 0/9]; p = 0.03). This supports the notion of immediate PTS, which typically occur in the field and may not reliably be deciphered from pathological posturing responses, as an entity distinct from early PTS. Status epilepticus was highly morbid, associated with a 70% mortality rate. Our previously identified markers may help risk-stratify patients who may warrant longer monitoring with continuous electroencephalography to detect and treat early PTS and corresponding status epilepticus risk.